Bonds of the child-family binomial before and after the diagnosis of childhood cancer* - Juliana Amaral Rockembach; Rosani Manfrin Muniz; Michele Cristiene Nachtigall Barboza; Aline Blaas Schiavon; Bruna Knob Pinto; Franciele Budziareck das Neves (Universidade Federal de Santa Maria, 2021)
Objective: to describe and analyze the bonds of the child-family binomial, before and after the diagnosis of cancer. Methods: This is a qualitative and descriptive study conducted with six families of children with cancer. Data collection occurred with guiding questions, construction of Genogram and Ecomap, from July to October 2017 in the participants' homes. Thematic analysis by Braun and Clarke was carried out. Results: The results were the broken bonds and those created before and after cancer. The main broken bonds were school activities, walks, living with the pet, and changes in food. The bonds created were new friendships in the hospital and the use of games and electronic games. Conclusion: recreational activities proved to be an interesting work tool to be used by health professionals, helping to build bonds, coping, and adapting the child and family.